Endovascular repair using parallel grafts to treat a suprarenal pancreatitis‐related abdominal aortic pseudoaneurysm. Issue 5 (8th March 2023) - Zacà, Sergio; Patruno, Isabella; Pulli, Raffaele; Angiletta, Domenico
Abstract: Arterial pseudoaneurysms represent an uncommon complication of acute pancreatic inflammation or chronic pancreatitis. We describe a contained rupture of a suprarenal abdominal aortic pseudoaneurysm. An aorto‐uni‐iliac stent‐graft was adopted as the aortic main body and was combined with two chimneys and two periscope stents for celiac/superior mesenteric artery and renal arteries, respectively. The procedure was complicated by the entrapment of the celiac sheath into the barbs of the aortic stent‐graft and the attempts to remove the sheath resulted in an upward migration of the stent‐grafts. A bail‐out endovascular procedure was used to reline the stent‐grafts and the pseudoaneurysmal sac was embolized with coils.